2014
DOI: 10.1155/2014/846385
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of ND:YAG Laser Posterior Capsulotomy Size on Refraction, Intraocular Pressure, and Macular Thickness

Abstract: Purpose. The aim of this study is to examine the influence of capsulotomy size on, spherical equivalent (SE), intraocular pressure (IOP), and macular thickness. Materials and Methods. Sixty-eight patients were examined preoperatively and 1, 4, and 12 weeks after Nd:YAG capsulotomy. Patients were divided into two groups based on the postoperative capsulotomy size. Changes in SE, IOP, and macular thickness were compared between two groups. Results. We found a higher hyperopic shift in large capsulotomy group. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
2
15

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 27 publications
(32 reference statements)
4
49
2
15
Order By: Relevance
“…They found that CMT thickness increased 1 week after treatment but 4 weeks after treatment CMT decreased to preoperative levels in both groups. (16) Ari et al who examined 30 patients according to the energy levels, they found significant increase in CMT in high energy group. (17) Another study from Turkey, Yılmaz et al studied about long term changes in macular thickness, they did not find significant change in CMT.…”
Section: Discussionmentioning
confidence: 97%
“…They found that CMT thickness increased 1 week after treatment but 4 weeks after treatment CMT decreased to preoperative levels in both groups. (16) Ari et al who examined 30 patients according to the energy levels, they found significant increase in CMT in high energy group. (17) Another study from Turkey, Yılmaz et al studied about long term changes in macular thickness, they did not find significant change in CMT.…”
Section: Discussionmentioning
confidence: 97%
“…In a study on the comparison of post-YAG capsulotomy size and macular thickness, it was stated that a rise in IOP could be related to a large capsulotomy but not a change in macular thickness (6) . Similarly, in a study performed by reviewing the applied force and complication, the authors (4) found that CMT change was significant in cases where >80 mj was applied, but insignificant when a force <80 mj was applied.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, retinal complications that may emerge later affect the choroid tissue. Various studies associated with anterior chamber and retinal changes in patients who have undergone YAG capsulotomy have been published (4)(5)(6) . However, to the best of our knowledge, there are no publications regarding choroi dal change.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have shown that hydrophilic IOLs lead to at least twice the number of Nd:YAG laser treatments when compared with hydrophobic lenses (1,13,17,18) . Although Nd:YAG laser capsulotomy is the standard treatment for PCO and is generally found to be safe and effective, it is also expensive and not free of complications (1,11,20) , including a significant rate of morbidity from postoperative complications. The most common complication is intraocular pressure elevation, while other complications include cystoid macular edema, retinal hemorrhage or detachment, iritis, vitreous prolapse, corneal damage, vitritis, iris damage, pupillary blockage, hyphema, IOL subluxation, and localized exacerbation of endophthalmitis (21,22) .…”
Section: Discussionmentioning
confidence: 99%